Integrating network pharmacology, IPA, and molecular docking to reveal the anti-osteoporosis effects of EA and EB via the FAK pathway - Ziheng Wei; Ziheng Wei; Fei You; Henghui Li; Si Wu; Fen Tang; Xiangyang Wan; Huizhong Dong; Wenxuan Huang; Songyan Gao; Bo Cai; Xiongsheng Chen; et al. (Frontiers in Pharmacology, 2025)
Osteoporosis is a widespread condition among the elderly, with a particularly high incidence in postmenopausal women aged 50 and above. This disease significantly increases the risk of fractures, adversely affecting the quality of life. Epimedium, a traditional Chinese medicinal herb, has been widely used in the treatment of osteoporosis due to its diverse therapeutic properties. However, Epimedium contains a complex mixture of compounds, including both beneficial and potentially harmful constituents. Therefore, there is a critical need to identify and isolate active monomeric compounds that can effectively treat osteoporosis, thereby enhancing the specificity and efficacy of treatment while reducing the intake of harmful substances. Through an integrated approach utilizing network pharmacology and extensive literature review, we identified five previously unreported anti-osteoporotic monomeric compounds from various traditional agents: Epimedin A (EA), Epimedin B (EB), Epimedoside A (EPA), 4-Hydroxybenzaldehyde (PHBA), and Baohuoside VI. We subsequently evaluated the effects of these compounds on bone marrow-derived macrophages (BMMs) and cranial preosteoblasts. Results from tartrate-resistant acid phosphatase (TRAP) staining and quantitative polymerase chain reaction (qPCR) demonstrated that EA, EB, and EPA significantly inhibited BMM differentiation into osteoclasts in a dose-dependent manner. In contrast, alkaline phosphatase (ALP) staining, Alizarin Red staining, and qPCR results showed that EA and EB promoted the differentiation of cranial preosteoblasts into osteoblasts in a dose-dependent fashion. Furthermore, intraperitoneal administration of EA and EB at doses of 5 mg/kg, 10 mg/kg, and 20 mg/kg in ovariectomized (OVX) mice resulted in a significant increase in bone mineral density and trabecular bone number compared to the OVX group (P < 0.05 compared to OVX group). These findings suggest that EA and EB may mitigate bone loss in OVX mice. Importantly, high doses of EA and EB did not exhibit pharmacological toxicity in various organs, as confirmed by hematoxylin and eosin (HE) staining. In exploring the underlying mechanisms, we found that EA and EB do not modulate the NF-κB signaling pathway, as indicated by the NFKB luciferase reporter assay. Western blot analysis further revealed that EA and EB might not affect osteoporosis progression via the MAPK (ERK and JNK) or NF-κB (P65 and IκBα) pathways. To elucidate the molecular targets, we utilized PharmMapper, Similarity Ensemble Approach, SwissTargetPrediction, and SuperPred to predict potential targets of EA and EB. Intersection analysis using the Ingenuity Pathway Analysis (IPA) database indicated that EA and EB regulate the focal adhesion kinase (FAK) signaling pathway. Molecular docking studies using Autodock confirmed the binding of EA and EB to FAK1 (binding free energy: −13.012 kJ/mol and −14.0164 kJ/mol) and FAK2 (binding free energy: −5.815 kJ/mol and −6.4852 kJ/mol). qPCR analysis further demonstrated that EA and EB significantly inhibited FAK1 and FAK2 gene expression in osteoclasts while promoting their expression in osteoblasts at very high doses. In conclusion, EA and EB, identified as active monomeric compounds in Epimedium, may exert their anti-osteoporotic effects by modulating the FAK signaling pathway, thereby enhancing bone mineral density and improving the quality of life for patients with osteoporosis. This study provides new insights into the pathogenesis of osteoporosis and the development of targeted anti-osteoporosis therapies. Further research is warranted to validate the role of EA and EB in modulating osteoporosis progression via the FAK signaling pathway.